Celastrol boosts fluconazole efficacy against vaginal candidiasis: in vitro and in vivo evidence - Fatma Al-zahraa A. Yehia; Hisham A Abbas; Tarek M. Ibrahim; Basem Mansour; Zuhier A. Awan; Mohammed W. Al-Rabia; Wesam H. Abdulaal; Mustafa Adnan Zeyadi; Solomon Z. Okbazghi; Tarek S. Ibrahim; Wael A. H. Hegazy; Salwa E. Gomaa (AMB Express)
Abstract Candida albicans is a commensal fungus that naturally inhabits the vagina. However, overgrowth of C. albicans can result in vulvovaginal candidiasis (VVC), one of the most prevalent fungal infections affecting women. The rapid emergence of azole resistance in C. albicans, in addition to the limited available antifungal agents, complicates the treatment and emphasizes the urgent need for novel therapeutic options. Efflux-mediated azole resistance is a common resistance mechanism in fluconazole (FLZ)-resistant C. albicans. Combination therapy using natural compounds is a potential approach that can restore fluconazole’s antifungal activity in azole-resistant isolates via efflux pump inhibition. This study aimed to evaluate the ability of celastrol, a natural triterpene, to retrieve FLZ antifungal activity against azole-resistant C. albicans in vitro and in vivo. Celastrol did not exhibit antifungal activity against the tested clinical isolates; however, the sub-MIC of celastrol inhibited rhodamine 6G (R6G) efflux and increased R6G accumulation inside celastrol-treated C. albicans cells. Synergy was spotted between celastrol and FLZ via a checkerboard assay. Quantification of m-RNA levels of efflux-mediated azole resistance genes within azole-resistant C. albicans demonstrated CDR1 overexpression. Upon celastrol treatment, a significant decline in ABC transporters transcript levels were detected. Moreover, molecular docking demonstrated that celastrol is a potential ABC efflux transporters blocker that successfully fits into target binding pockets. A negligible hemolytic effect of celastrol against human erythrocytes was observed. In the in vivo model of VVC, the combination of FLZ and celastrol in vaginal gel revealed a drastic reduction in the fungal burden with apparently normal vaginal tissue. Celastrol promising in vitro and in vivo findings strengthen its future use for the treatment of azole-resistant C. albicans.